Sequência didática sobre o sistema digestório: avaliação da sua contribuição na aprendizagem discente e no trabalho docente - Assandri, Leovane da Silva (2024)
One of the difficulties pointed out by researchers in the field and teachers who work directly in the classroom when teaching Biology concepts, both in the specific curricular component and in the Science component, is a very descriptive approach, with excessive use of scientific terms. This, together with the lack of contextualization or approximation to the contemporary world in which the student lives, end up making learning in this discipline difficult. With the possibilities that have been discussed for teaching that has more meaning for the student, it is necessary for the teacher to rethink his/her teaching action, seeking new ways to approach the content. Thus, the production and provision of teaching materials that assist the teacher in his/her pedagogical work is relevant and for this reason the educational product proposed in this work involves a didactic sequence (DS) to approach the digestive system using teaching tools that place the student in a more dynamic position. Taking these points into account, the following question was formulated for this research: What contributions can a didactic sequence on the digestive system, based on the 3 MPs, promote in teaching action and student learning? Therefore, the objective of this work was to analyze a didactic sequence, an educational product of this research, to address the digestive system in Elementary School, regarding its contribution to the learning of knowledge objects related to the topic, by students. The SD was constructed based on the dynamics of the three pedagogical moments, contemplating the objectives that are suggested by the theoretical framework of the dynamics. The SD includes resources such as video, the active Think Pair Share (TPS) methodology and virtual games, among others. The research was qualitative in nature, of the applied research type and the data collection instruments were the teacher's logbook, a questionnaire to identify the students' prior knowledge and an assessment activity of the students' learning. The SD was applied in a public school in the city of Herval d'Oeste (SC), with 30 students of the 7th grade of Elementary School - Final years. The results indicated that the SD was successful; the students performed well in the games that involved evaluating the topics covered about the digestive system; they interacted well with the proposed activities and brought their experience to the discussions that unfolded as the subjects were addressed. Thus, the 3 MPs, due to their profile that encourages the teacher to problematize and contextualize the approach to the content, allowed for satisfactory results for student learning. For the teacher, these results indicate that it is a way to make their action in the classroom meaningful for the student. The educational product developed in this dissertation is freely accessible and is available on the EduCapes website under the number http://educapes.capes.gov.br/handle/capes/917677.